2013
DOI: 10.1002/pssr.201308085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecular tilt angle on the absorption spectra of pentacene:perfluoropentacene blends

Abstract: We investigate the relation between the optical properties and the average molecular tilt angle for blends of pentacene and perfluoropentacene, which can be considered as a prototypical donor–acceptor complex. Combining near‐edge X‐ray absorption fine‐structure spectroscopy and optical spectroscopy we study thin films of these compounds prepared at three different substrate temperatures Tsub. For Tsub =180 K we observe a larger average tilt angle than for blends prepared at higher substrate temperatures. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…• Phase separation: If the two materials are sterically incompatible [62] or the interaction energies within the single materials are significantly more attractive than the inter-species energy (χ > 2) usually a phase separation of the materials is observed. • Ordered complex: An ordered complex is usually formed if the interaction energy between the two different materials is higher than the interaction energies within one species and the materials are sterically compatible [61,63,64].…”
Section: Phase Separation In Bhj Geometriesmentioning
confidence: 99%
“…• Phase separation: If the two materials are sterically incompatible [62] or the interaction energies within the single materials are significantly more attractive than the inter-species energy (χ > 2) usually a phase separation of the materials is observed. • Ordered complex: An ordered complex is usually formed if the interaction energy between the two different materials is higher than the interaction energies within one species and the materials are sterically compatible [61,63,64].…”
Section: Phase Separation In Bhj Geometriesmentioning
confidence: 99%
“…19 Moreover, the accompanying theoretical analysis of the fluorine NEXAFS spectra, carried out within the framework of the transition potential method, has actually yielded a mixed π*/σ* character, which in turn hampers a quantitative analysis of the F 1s dichroism in pure and mixed systems. 19,20 In their study Oteyza et al used monolayer films of PFCuPc and PFP adsorbed on noble metals. 19 While this approach provides planar adsorption geometries in general, it remains a priori unclear whether the NEXAFS signature is affected by electronic adsorbate-substrate coupling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a previous study of PFCuPc and perfluorinated pentacene (PFP) inversed dichroisms have been reported for the carbon and fluorine K-edge NEXAFS signatures . Moreover, the accompanying theoretical analysis of the fluorine NEXAFS spectra, carried out within the framework of the transition potential method, has actually yielded a mixed π*/σ* character, which in turn hampers a quantitative analysis of the F 1s dichroism in pure and mixed systems. , …”
Section: Introductionmentioning
confidence: 99%
“…This result coincides with that obtained by Raman spectroscopy. The absorption spectra of pentacene films also exhibit the same phenomena (see Supporting Information, Figure S4); that is, the red shift is observed in the curves of FOS films as the growth temperature increases and the trend of the curve shift of neat pentacene films is reverse. This similar result shows that the interaction of electron coupling in FOS films must be influenced by the doping of Ni atoms.…”
Section: Results and Discussionmentioning
confidence: 60%